Multi-National Banks and the Management of Monetary Policy in the United States: Discussion - Noyes, Guy E. (Journal of Finance, 1973)
Guy E. Noyes, Multi-National Banks and the Management of Monetary Policy in the United States: Discussion, The Journal of Finance, Vol. 28, No. 2, Papers and Proceedings of the Thirty-First Annual Meeting of the American Finance Association Toronto, Canada, December 28-30, 1972 (May, 1973), pp. 462-465